The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1371/journal.pone.0183633
|View full text |Cite
|
Sign up to set email alerts
|

Excessive use of WeChat, social interaction and locus of control among college students in China

Abstract: In China, the number of college students using mobile phone based messaging and social networking applications like WeChat is increasing rapidly. However, there has been minimal research into the addictive nature of these applications and the psychological characteristics associate with their excessive use. There is also no published scale available for assessing excessive use of WeChat and similar applications. In the current study, we collected data from 1,245 college students in China (715 females) and deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 63 publications
2
47
0
Order By: Relevance
“…Trained out-patient doctors will introduce the details of the trial to each potential participant during a clinic visit. The trial coordinator will contact the interested participant by mobile phone and WeChat, a very popular social networking app in China [ 34 ]. Eligible participants will be introduced in the trial.…”
Section: Methodsmentioning
confidence: 99%
“…Trained out-patient doctors will introduce the details of the trial to each potential participant during a clinic visit. The trial coordinator will contact the interested participant by mobile phone and WeChat, a very popular social networking app in China [ 34 ]. Eligible participants will be introduced in the trial.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, PSMU has been investigated in relation to specific SMSs such as Facebook (Andreassen et al 2012;Hong et al 2014), Twitter (Davenport et al 2014;Kircaburun 2016a;Kim et al 2008), Instagram (Kircaburun and Griffiths 2018a, b), Snapchat (Punyanunt-Carter et al 2017), WeChat (Hou et al 2017), Youtube (Balakrishnan and Griffiths 2017), and social media in general (Andreassen et al 2017;Bányai et al 2017;Kircaburun 2016b;Kircaburun et al 2018a, b). These studies have shown that PSMU is associated with various psychological, personality, and individual difference factors.…”
Section: Uses and Gratificationsmentioning
confidence: 99%
“…Given that, researchers should abstain from overpathologizing everyday life behaviors (Billieux et al, 2015), it is important to mention that SNS use can have positive effects on well-being. In this context, research observed that non-problematic use of SNSs was associated with higher external locus of control, greater online social interaction skills and higher life satisfaction (Nadkarni and Hofmann, 2012;Liu et al, 2016;Hou et al, 2017;. Active (vs. passive) use of SNSs together with meaningful interaction between people represents nonproblematic use of SNSs (e.g., Escobar-Viera et al, 2018).…”
Section: Introductionmentioning
confidence: 99%